Oportunidades de corrupción y pandemia: El compliance gubernamental como un protector eficaz al interior de las organizaciones públicas - Madrid Valerio, Cecilia (2020)
This essay postulates that public compliance programs implemented in essential sectors of public administration particularly exposed to corrupt practices during the response to the Covid-19 pandemic will help to reduce the risk of corruption, or at the very least, enable the identifying of such risk and its reporting to the relevant authorities. In this way, any individuals inclined to abuse their position in the future will be aware of the existence of effective protections within public sector organizations.